2009
DOI: 10.1007/s00011-009-0117-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bilastine compared with cetirizine, fexofenadine, and placebo on allergen-induced nasal and ocular symptoms in patients exposed to aeroallergen in the Vienna Challenge Chamber

Abstract: Bilastine had a rapid onset of action, within 1 h, and a long duration of action, greater than 26 h. Cetirizine was similar. Fexofenadine was similar on day 1 but less effective on day 2, indicating a shorter duration of action. Bilastine, like cetirizine and fexofenadine, was safe and well tolerated in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 25 publications
1
59
0
3
Order By: Relevance
“…Promising H 1 -antihistamine/glucocorticoid nasal formulations are being investigated. [23][24][25][26][27][28] H 1 -antihistamines act as inverse agonists that combine with and stabilize the inactive conformation of the H 1 -receptor, shifting the equilibrium toward the inactive state. For more than 50 years, they were described as H 1 -receptor antagonists or H 1 -receptor blockers; however, these out-of-date terms do not accurately reflect their molecular mechanism of action ( Fig 2).…”
Section: H 1 -Antihistaminesmentioning
confidence: 99%
“…Promising H 1 -antihistamine/glucocorticoid nasal formulations are being investigated. [23][24][25][26][27][28] H 1 -antihistamines act as inverse agonists that combine with and stabilize the inactive conformation of the H 1 -receptor, shifting the equilibrium toward the inactive state. For more than 50 years, they were described as H 1 -receptor antagonists or H 1 -receptor blockers; however, these out-of-date terms do not accurately reflect their molecular mechanism of action ( Fig 2).…”
Section: H 1 -Antihistaminesmentioning
confidence: 99%
“…Furthermore, the overall efficacy results demonstrated that bilastine was of similar efficacy to levocetirizine [14]. In the nose, a double-blind cross-over study in which 75 allergic volunteers were challenged with grass pollen in the Vienna Challenge Chamber showed bilastine to be equally effective as cetirizine and fexofenadine but the results obtained suggest that it has a longer duration than fexofenadine [15], while in two 14-day trials in seasonal allergic rhinitis, bilastine was shown to be of similar efficacy to daily dosage with 10 mg cetirizine and 5 mg desloratadine [16,17].…”
Section: Introductionmentioning
confidence: 96%
“…Başka bir çalışmada çim allerjisi bulunan AR'li hastalarda Bilastine'nin feksofenadinden daha etkili ve en az setirizin kadar etkili olduğu gösterilmiştir. Diğer bir çalışmada Bilastine'nin desloratadin ile karşılaştırılabilir bir klinik etkisi bulunmuştur (78). Bilastine aç olarak alındığında hızlı bir şekilde emilir ve önemli bir kısmı metabolize olmaz.…”
Section: Diğer Tedavilerunclassified